Teacher decision-making, dynamical systems and processability theory. Issue 2 (15th November 2022) - Nicholas, Howard; Pienemann, Manfred; Lenzing, Anke
Abstract : We demonstrate the possibility of a principled integration of the predictable characteristics of learner language and the unpredictability of socially embedded language use. In contrast with the claim that dynamical systems' behaviour is universally unpredictable, we demonstrate that dynamical systems theory embraces predictability as a fundamental tenet. We refer to the utterance-oriented basis of processability theory for insights into predictions about L2 learning sequences that simultaneously embrace learner variation. We sketch empirical findings offering ways to connect variation and learner pathways. These findings provide evidence of how learner options emerge that are linked to unproductive pathways. We argue that building on these insights enables teachers to avoid the DST-inspired chaos narrative and locate specific regularities in learners' dynamic language use. We show that interpersonal variation and intrapersonal variability can be integrated with a pedagogic perspective on predictable developmental sequences. We outline how this perspective offers nuanced support for teacher decision-making.